PERBEDAAN KEMAMPUAN PENALARAN MATEMATIKA SISWA ANTARA TEKNIK PEMBELAJARAN PROBING PROMPTING DENGAN METODE PEMBELAJARAN KONVENSIONAL DI KELAS VII SMP 17 AGUSTUS 1945 SURABAYA (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2015)
Orientation mathematics are mathematical reasoning abilities. Reasoning is a process or activity is thought to draw the right conclusions based on some of the statements that have been proven or assumed to be true. Students require reasoning ability in solving mathematical problems that involve critical thinking, systematic, logical, and creative. Through the mathematical reasoning students can apply for the alleged then compile evidence, manipulation, and draw conclusions correctly and precisely of the problem or a math problem. Mathematical reasoning skills students are low is one of the fundamental problems in mathematics today. The low student learning outcomes are influenced by many factors, one of which is the use of teaching methods that are less effective and efficient cause unbalance cognitive abilities, affective, and psychomotor student. Learning methods commonly used by mathematics teachers are conventional teaching methods that rely on lectures and main tools blackboard so that students tend to be passive and less involved in the classroom. Conventional teaching methods do not provide the opportunity for students to think and can hamper students' mathematical reasoning abilities. One of the techniques taught are considered accommodative can attract students and increase the activity of thinking students are learning techniques probing prompting. Which is a technique of learning by the teacher presents a series of questions that are guiding and dug so that a process of thinking that links students' knowledge and experience with new knowledge that is being studied.